THE MODERATING EFFECT OF INTELLECTUAL CAPITAL ON THE RELATIONSHIP BETWEEN PROFITABILITY, ECONOMIC VALUE ADDED, AND STOCK RETURN (Accounting Study Program, Universitas Ciputra Surabaya, 2022)
The purpose of this study is to determine the impact of ROA, ROE, EPS, and EVA on stock returns through intellectual capital as a moderation variable. The population of this research is Kompas 100 index companies for 2012-2019. Samples taken were 32 companies using purposive sampling. The method of collecting data used indirect observation and using multiple linear regression analysis. The results indicate that ROA, ROE, EPS, and EVA do not affect stock return, intellectual capital does not moderate the relation between ROA and stock return, intellectual capital moderate the relation between ROE and stock return, intellectual capital doesnot moderate the relation between EPS and stock return, intellectual capital does not moderate the relation between EVA and stock return. Keywords: profitability, market, EVA, intellectual capital, stock.